Sarcopenia in Rheumatic Diseases: A Hidden Issue of Concern - Eleni C. Pardali; Markos Klonizakis; Dimitrios G. Goulis; Sousana K. Papadopoulou; Christos Cholevas; Constantinos Giaginis; Christina Tsigalou; Dimitrios P. Bogdanos; Maria G. Grammatikopoulou (Diseases)
Sarcopenia is characterized by a loss of muscle mass and function, with significant implications for the physical performance of the affected people. Although commonly associated with aging, disease-related sarcopenia is of great clinical importance, particularly as it impacts disease progression and outcomes. Individuals with rheumatic diseases (RDs), including rheumatoid arthritis, systemic sclerosis, spondyloarthritides, systemic lupus erythematosus, fibromyalgia, myositis, or vasculitis, exhibit a high prevalence of sarcopenia, which exacerbates their clinical symptoms and contributes to poorer disease outcomes. Chronic inflammation influences muscle tissue degradation, causing a decline in physical performance. Apart from the apparent clinical manifestations, patients with RDs also use pharmacological treatments that negatively impact muscle mass further, increasing the risk of sarcopenia. Nutrition (diet and dietary supplements) and exercise interventions have been recommended as protective measures for sarcopenia as they may mitigate its adverse events. The present narrative review seeks to explore the methods used to assess sarcopenia in patients with RDs, its prevalence among them, and the challenges faced by the affected individuals, while critically assessing the appropriateness and limitations of current sarcopenia assessment tools in the context of RDs.